Business Schools and Management Research: A UK Perspective - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2009)
In recent years, the role and value of management research is being increasingly challenged because of the perceived imbalance between its rigour and relevance. The purpose of this paper is to review the progress of management research in the UK and focuses particularly on the need for sensible evaluation of the impact of management research. The paper outlines the research challenges faced by business schools from a UK perspective. It draws upon the author's experiences and the results of an analytic study of Economic and Social Research Council-sponsored research undertaken by the author in 2008. There is a perception that management as a discipline, and its resulting research profile, may be more difficult to evaluate than its social science sub-disciplines such as economics, psychology, and sociology. In some instances, management research is perceived as of lower quality and capacity shortages of high-quality management research scholars have also been identified. The dominant research challenges are both to successfully design practice-informed management scholarship and to carefully address the dissemination of results in order to influence the impact of management research on practice. The paper suggests that an increasing focus on practice and cross-cutting inter-disciplinary topics, such as climate change or the role of finance in society, should form a significant element of the research agendas of business schools. In any event, it is argued that cutting-edge research should be the overarching aim of business schools in a knowledge society.